The Use of Velodrome Tests to Evaluate Aerodynamic Drag in Professional Cyclists - García-López, J.; Ogueta-Alday, A.; Larrazabal, J.; Rodríguez-Marroyo, J. A. (International Journal of Sports Medicine, 2014)
The purpose of this study was to analyse the validity, reliability and sensitivity of velodrome tests to detect small changes in aerodynamic drag in cycling. 12 professional cyclists were assessed to obtain the drag area (SCx) during wind tunnel and velodrome tests. Incremental and steady-state protocols were performed in the velodrome with a portable power meter, and 6 bicycle positions were analysed and compared that involved lowering the handlebars and advancing the pads between 2–5 cm. A significant relationship (r=0.88, p<0.001) between the SCx in the wind tunnel and velodrome tests was found (0.240±0.007 and 0.237±0.008 m2, respectively). The velodrome tests underestimated the SCx (0.0035±0.0038 m2 and p<0.01), which decreased (p<0.001) when the bicycle speed increased (0.0013 m2 each 1 km · h−1). The SCx values showed high reliability during the steady-state (r=0.99, p<0.001) and incremental protocols (r=0.94, p<0.001). Small changes in the aerodynamic position affected the SCx (p<0.001), which decreased by 0.011±0.007 m2 (4.6±2.9%, 95% CI=2.7–6.4%). In conclusion, the validity, reliability and sensitivity of velodrome tests to detect small changes in aerodynamic drag in cycling were demonstrated. Although SCx values were not interchangeable between different studies, the velodrome tests presented advantages with respect to the wind tunnel tests.
Keywords: cycling; biomechanics; aerodynamics; time-trial